Scientific and Regulatory Policy Committee Best Practices*: Documentation of Sexual Maturity by Microscopic Evaluation in Nonclinical Safety Studies. (July 2021) - Vidal, Justin D.; Colman, Karyn; Bhaskaran, Manoj; de Rijk, Eveline; Fegley, Darren; Halpern, Wendy; Jacob, Binod; Kandori, Hitoshi; Manickam, Balasubramanian; McKeag, Sean; Parker, George A.; Regan, Karen S.; et al.
The sexual maturity status of animals in nonclinical safety studies can have a significant impact on the microscopic assessment of the reproductive system, the interpretation of potential test article–related findings, and ultimately the assessment of potential risk to humans. However, the assessment and documentation of sexual maturity for animals in nonclinical safety studies is not conducted in a consistent manner across the pharmaceutical and chemical industries. The Scientific and Regulatory Policy Committee of the Society of Toxicologic Pathology convened an international working group of pathologists and nonclinical safety scientists with expertise in the reproductive system, pathology nomenclature, and Standard for Exchange of Nonclinical Data requirements. This article describes the best practices for documentation of the light microscopic assessment of sexual maturity in males and females for both rodent and nonrodent nonclinical safety studies. In addition, a review of the microscopic features of the immature, peripubertal, and mature male and female reproductive system and general considerations for study types and reporting are provided to aid the study pathologist tasked with documentation of sexual maturity.